KAJIAN PERBANDINGAN UNJUK-KERJA JARINGAN MPLS DAN NON MPLS: STUDI KASUS JARINGAN KOMPUTER JURUSAN TEKNIK ELEKTRO POLITEKNIK NEGERI BANDUNG - , Malayusfi, Dr. Eng. Ir. Risanuri Hidayat, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Computer networks at Jurusan Teknik Elektro Politeknik Negeri Bandung (JTE Polban), which have limited networks capacities need to apply networking arrangement that is managing allocation of networks element, so that it will gives good quality of service (QoS). The purpose to implementation QoS in Multi Protocol Label Switching (MPLS) is to ascertain how servicing of MPLS when transmitting real time packet traffic data. This thesis report constitutes performance simulation analysis of internetworking in JTE Polban by designing Multi Protocol Label Switching (MPLS) network as a backbone. Principle of MPLS is decreasing route seeking to be passed by packet in each router. Research inputs are transmission time, delay, packet loss, throughput and utilization between end-to-end systems in this internetworking. Analysis was done by generating different types of traffic application services, i.e. Email, Web Browsing, Video Streaming and FTP in each Label Switching Path (LSP) of MPLS network. Testing and simulation were done by applying four scenarios, i.e. scenario with one router, scenario with two routers, scenario MPLS and scenario MPLS TE using OPNET. From testing and analysis simulation result was obtained that there were an efficient in MPLS network and that MPLS network capable to give QoS better than non-MPLS network. These research results are testifying that transmission time of data packet sent in MPLS network increase by ten times and network capacity also increase by 150%. So that MPLS network capable to give networking performance with service level more optimal and suitable for real time data packet sent.